Higher Order Thinking Skills (HOTS): An Analysis Based On Surah Al-Hajj Verse 46 - Ismail, Nor Hanani; Makhsin, Mardzelah; Rofie, Mohamad Khadafi; Omar, Salmah (Selcuk University, 2021)
Higher Order Thinking Skills (HOTS) is the ability to apply knowledge, skills and values in reasoning and reflection. Islam associates knowledge with the process of thinking. Terms such as tafakkur and ta„aqul (thinking) are used to describe the thought process. The process of tafakkur and ta?aqulis accompanied by a tool used to think and comprehend,which is the qalb (heart). This is stated in surah al-Hajj, verse 46. This picture gives rise to two questions. Firstly, what is the scholar's view of the verse? Secondly, what is the relationship between HOTS and the function of qalbwhich is found in surah al-Hajj verse 46? This study has two main purposes. First, to analyze the scholars' views on verse 46 of Surah al-Hajj. Second, to formulate the relationship of qalb as found in Surah al-Hajj verse 46 with HOTS. This study aims to answer both these questions through content and textual analyses of various literature. For the first question, this study exhibits five main elements found in verse 46 of Surah al-Hajj. For the second question, this study concludes that the function of qalb can further strengthen the concept of HOTS